(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
Relevance. Tactical preparation in field hockey has its own features which are reflected in the sequence of studying tactical methods, interactions, schemes, and relevant applications of different forms and methods of training. The development of the theoretical basis is the main prerequisite for the implementation of tactical training programming into the process of long-term improvement. The purpose of the study is to provide a theoretical substantiation of tactical training programming in field hockey. The presentation of the main material. Despite the constant modernization of the system of training athletes, as well as the existing legislative framework, aimed at innovative transformations in sports, today information on the use of interactive means in the training of athletes of different qualifications in field hockey is almost absent, which does not meet modern demands of practice. It is proposed to use computer games as interactive tools that allow students to learn the necessary theoretical material from the section on tactics in a relaxed form, as well as promote the development of game thinking and other psychomotor abilities in athletes. The level of integration of theoretical and practical components of tactical training and, as a result, its effectiveness, can be significantly improved if tactical training is purposefully and systematically programmed with using its various forms throughout the long-term process of sports training. Conclusions. The use of digital technologies and specialized software for programming of tactical training and their wide application in the form of multimedia support of the training process and computer games (solving special game tasks) in the process of independent training in accordance with the tasks of each stage of long-term improvement is a necessary condition for the organization of effective work of the field hockey coaching staff in modern conditions.